2022
DOI: 10.1093/infdis/jiac304
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Severe Acute Respiratory Syndrome Coronavirus 2 Antigen–Specific Systemic Immune Responses in Multisystem Inflammatory Syndrome in Children and Reversal After Recovery

Abstract: Background Multisystem inflammatory syndrome in children (MIS-C) presents with inflammation and pathology of multiple organs in the pediatric population in the weeks following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Methods We characterized the SARS-CoV-2 antigen–specific cytokine and chemokine responses in children with MIS-C, coronavirus disease 2019 (COVID-19), and other infectious diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previously, our group has shown an increased level of cytokines in the antigen-specific culture supernatants including IFNγ, IL-2, IL-4, IL-13, and IL-17 in MIS-C in comparison with acute COVID-19 and other infectious diseases ( 16 ). However, in the current study, we have elucidated the antigen-specific cellular immune responses, and our results revealed that enhanced frequencies of SARS-CoV-2-specific CD4 + and CD8 + T cells expressing type 1 and type 17 cytokines are major characteristics of the MIS-C immune profile.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, our group has shown an increased level of cytokines in the antigen-specific culture supernatants including IFNγ, IL-2, IL-4, IL-13, and IL-17 in MIS-C in comparison with acute COVID-19 and other infectious diseases ( 16 ). However, in the current study, we have elucidated the antigen-specific cellular immune responses, and our results revealed that enhanced frequencies of SARS-CoV-2-specific CD4 + and CD8 + T cells expressing type 1 and type 17 cytokines are major characteristics of the MIS-C immune profile.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, HLA-genotype alterations in the T cells of children with MIS were reported as MIS-C biomarkers (15). Similarly, there are studies demonstrating that following Tcell stimulation by SARS-CoV-2-specific antigens in children with MIS, there was a dysregulated increase of Type 1, Type 2, Type 17, and other pro-inflammatory cytokines and chemokines when compared to the healthy controls (16). It was also reported that T cells with specific β-chain receptors are minimally responsive to SARS-CoV-2-specific antigens but do respond to non-viral antigens in the majority of the children with MIS (17,18).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is only one study by Rybkina et al based on fresh blood collection and PBMCs isolation that also showed distinct cellular immune responses between MIS-C and uncomplicated COVID-19 patients, however aim of the study was to identify certain transcriptional signature differences of TCR gene expression between MIS-C acute and convalescent phase 14 . Kumar et al performed in fresh, non-freeze thawed blood of MIS-C patients, however no PBMCs isolation was implemented 15 . It is important to interpretate results regarding cytokines from non-speci c in amed tissues (serum, plasma, whole blood) from other studies that speci cally re ect the activation of CD4 + and CD8 + , both of which play a key role in conditions characterized by immune dysregulation, such as MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…The first class of clinical parameters reported associated hyperinflammation, including elevated acute phase reactants [ 5 , 41 , 44 , 47 ], accompanied by increased biomarkers of coagulation [ 41 , 47 , 48 , 49 ] and cardiac function [ 39 , 43 , 50 , 51 ]. In the acute phase of MIS-C, exacerbation of cytokines as some interleukins (IL), tumor necrosis factor-alpha (TNF-a), and interferon-gamma (INF-γ) levels have been reported [ 48 , 51 , 52 , 53 , 54 , 55 ], as well as chemokines including the IL-2 receptor agonist, C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligands 8, 9 and 10 (CXCL8, CXCL9, CXCL10), and monocyte chemoattractant protein (MCP)-1 [ 42 , 48 , 56 , 57 , 58 ]. In addition, changes in leukocyte count and distribution are considered as circulating biomarkers [ 54 , 59 , 60 , 61 , 62 ], as well as significant changes in serum biomarkers such as albumin [ 26 , 44 , 63 , 64 ], lactate dehydrogenase (LDH) [ 41 ], creatinine [ 41 , 48 ], sodium [ 48 , 57 , 63 ], triglycerides [ 65 , 66 ] and zonulin [ 67 , 68 ] ( Table 1 ).…”
Section: Inflammatory Markers In Mis-cmentioning
confidence: 99%